1977
DOI: 10.1148/124.3.763
|View full text |Cite
|
Sign up to set email alerts
|

Roentgenographic Features of American Burkitt's Lymphoma

Abstract: Studies of American Burkitt's lymphoma in 12 children showed a high incidence of abdominal involvement, including ileocecal masses with intussusception, retroperitoneal extension, and diffuse bowel involvement. Pleural effusions were common, and 2 patients had pulmonary nodules. Three patients had diffuse renal involvement. The mandibles and other bones were not affected in any of the 9 patients tested. The first 2 patients survived 0.5 to 8.5 months; the last 2 were treated much more aggressively and were sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
9
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
4
9
1
Order By: Relevance
“…This high incidence of pleural effusions and no evidence of mediastinal and hilar adenopathy corresponds with previous reports, though one study of 40 patients found three with hilar and mediastinal adenopathy at presentation [8,9]. The other lymphomas have a high incidence of mediastinal adenopathy, though other solid tumors of childhood do not usually present with either mediastinal or hilar adenopathy or pleural effusion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This high incidence of pleural effusions and no evidence of mediastinal and hilar adenopathy corresponds with previous reports, though one study of 40 patients found three with hilar and mediastinal adenopathy at presentation [8,9]. The other lymphomas have a high incidence of mediastinal adenopathy, though other solid tumors of childhood do not usually present with either mediastinal or hilar adenopathy or pleural effusion.…”
Section: Discussionsupporting
confidence: 89%
“…Clinically, Burkitt lymphoma can masquerade as many disease complexes, making the diagnosis difficult. A variety of radiologic procedures for diagnosis and staging have been described in the literature, depending on the mode of presentation of the disease [1][2][3][4][5][6][7][8]. Much of this literature has compared American Burkitt lymphoma with African Burkitt lymphoma.…”
mentioning
confidence: 99%
“…Hydronephrosis is a recognized complication of retroperitoneal or pelvic Burkitt's lymphoma and has been reported in 28 percent of patients (31, a figure comparable to that in the present series. Tumor infiltration is the other most commonly encountered renal abnormality in American Burkitt's lymphoma (13,21). Our two cases of renal lymphoma showed poorly defined peripheral anechoic masses within mildly enlarged kidneys.…”
Section: Discussionmentioning
confidence: 53%
“…This is consistent with the reported absence of lumbar para-aortic lymph 's lymphoma (3,7). The large tumors of Burkitt's lymphoma tend to be located in the lower abdomen or pelvis because of the high incidence of ileocecal (13,141, mesenteric, or ovarian (15) involvement. Local or diffuse involvement of the retroperitoneum is not infrequently seen a t surgery, and it may be associated with ureteric obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation